(untitled) (Research, Society and Development, 2023)
This work analyzes whether the hypothesis of sexual transmission by fluids, of the Monkeypox disease, is true and if it can be considered the prevalent one among the other forms of transmission. This is an integrative literature review that consulted the PubMed, Virtual Health Library and Scielo databases in October 2022, comparing articles published between 2018 and October 2022. After the screening steps, 12 articles were included. The main results were grouped into two categories: a) they suggested the hypothesis of sexual transmission as a highly relevant route in contact with Monkeypox Virus (MPXV) and b) they demonstrated the numerical prevalence of sexual transmission in confirmed cases of MPXV. Seven studies suggested the hypothesis of sexual transmission as a highly relevant route in contact with MPXV, while five studies demonstrated the numerical prevalence of sexual transmission in confirmed cases of MPXV. There is an association between MPXV and Sexually Transmitted Infections (STIs), such as HIV, and it is pertinent to recognize the sexual transmission route, by fluids, of monkeypox, as one of the main routes of contamination.